1996
DOI: 10.1128/mcb.16.7.3587
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Extrachromosomal Circular Amplicons with Direct or Inverted Duplications in Drug-Resistant Leishmania tarentolae

Abstract: Selection for methotrexate resistance in Leishmania spp. is often associated with amplification of the H locus short-chain dehydrogenase-reductase gene ptr1 as part of extrachromosomal elements. Extensive sequences are always coamplified and often contain inverted duplications, most likely formed by the annealing of inverted repeats present at the H locus. By gene targeting mediated by homologous recombination, several repeated sequences were introduced in the vicinity of ptr1. Selection for methotrexate resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
7

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 47 publications
(93 reference statements)
2
66
0
7
Order By: Relevance
“…Second, a DNA IR also serves either as an "at-risk-motif" or a "fragile site" to regulate large palindrome formation in S. cerevisiae when DNA replication, repair, and checkpoint function are compromised (14,18). Furthermore, IR sequences preexisting in the genome are found at the centers of palindromes in Leishmania and Schizosaccharomyces pombe (2,11). This DNA IR-facilitated model of gene amplification predicts that palindrome formation is in part regulated by the presence of DNA IRs and occurs nonrandomly in the genome, which may provide a mechanistic basis for the nonrandom distribution of DNA palindromes in human cancer cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Second, a DNA IR also serves either as an "at-risk-motif" or a "fragile site" to regulate large palindrome formation in S. cerevisiae when DNA replication, repair, and checkpoint function are compromised (14,18). Furthermore, IR sequences preexisting in the genome are found at the centers of palindromes in Leishmania and Schizosaccharomyces pombe (2,11). This DNA IR-facilitated model of gene amplification predicts that palindrome formation is in part regulated by the presence of DNA IRs and occurs nonrandomly in the genome, which may provide a mechanistic basis for the nonrandom distribution of DNA palindromes in human cancer cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…The copy number of its chromosome may vary either in wild-type (WT) cells or in drug-resistant mutants (31)(32)(33)(34), and the ploidy of specific chromosomes of individual cells may differ within a population, a concept known as mosaic aneuploidy (35). Leishmania also amplifies specific portions of its genome by gene rearrangements at the level of direct or inverted repeated sequences, leading to small extrachromosomal circular or linear amplicons (32,34,36,37). Recently, we found that repeated sequences are widespread in the Leishmania genome and that there is constitutive amplification at the level of these repeated sequences (J. M. Ubeda et al, submitted for publication).…”
mentioning
confidence: 99%
“…The circular and linear amplicons in MTX-resistant Leishmania tropica and Leishmania tarentolae were derived from the H locus. Furthermore, analysis of the MTX-resistant mutants at different steps of drug selection showed that the linear amplicons were formed during the first steps of selection, while the circles appeared later, thus suggesting a linear precursor-circular product relationship (11,12). A similar precursor-product relationship has also been proposed for formation of the CD1 circles derived from the linear amplicon LD1 (13).…”
Section: Introductionmentioning
confidence: 71%
“…Amplification of the H locus upon MTX selection has been described in several Leishmania species (21)(22)(23). The extrachromosomal circular amplicons derived from the L.tarentolae H locus have been characterized and were shown to be created at the level of direct or inverted repeated sequences flanking ptr1 (9,12,24). In this study, by tagging the individual alleles of the H locus with different dominant markers, we were able to follow the formation of amplicons at different steps of MTX selection.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation